Characterization of pncA Mutations and Prediction of PZA Resistance in Mycobacterium tuberculosis Clinical Isolates From Chongqing, China - Li, Kun; Yang, Zhongping; Gu, Jing; Luo, Ming; Deng, Jiaoyu; Chen, Yaokai (Frontiers in Microbiology, 2021)
Pyrazinamide (PZA) is widely used to treat drug-sensitive or multidrug resistance tuberculosis. However, conventional PZA susceptibility tests of clinical isolates are rather difficult because of the requirement of acid pH. Since resistance to pyrazinamide is primary mediated by mutation of pncA, an alternative way of PZA susceptibility test is to analyze the pyrazinamidase activities of Mycobacterium tuberculosis clinical isolates. Therefore, a database containing the full spectrum of pncA mutations along with pyrazinamidase activities will be beneficial. To characterize mutations of pncA in M. tuberculosis from Chongqing, China, the pncA gene was sequenced and analyzed in 465 clinical isolates. A total of 124 types of mutations were identified in 424 drug resistant isolates, while no mutation was identified in the 31 pan-susceptible isolates. Ninety-four of the 124 mutations had been previously reported, and thirty new mutations were identified. Based on reported literatures, 294 isolates could be predicted resistant to pyrazinamide. Furthermore, pyrazinamidase activities of the thirty new mutations were tested using the Escherichia coli pncA gene knockout strain. The results showed that 24 of these new mutations (28 isolates) led to loss of pyrazinamidase activity and 6 (8 isolates) of them did not. Taken together, 322 isolates with pncA mutations could be predicted to be PZA resistant among the 424 drug resistant isolates tested. Analysis of pncA mutations and their effects on pyrazinamidase activity will not only enrich our knowledge of comprehensive pncA mutations related with PZA resistance, but also facilitate rapid molecular diagnosis of pyrazinamide resistance in M. tuberculosis.